Darkness visible the Sculptor's Cave, Covesea, from the Bronze Age to the Picts - Armit, Ian; Büster, Lindsey ca. 20./21. Jh (Society of Antiquaries of Scotland, 2020)
The Sculptor?s Cave is one of the most enigmatic prehistoric sites in Britain. Excavated in the 1920s and?1970s, new analysis of the archive has revealed a complex history of funerary and ritual activity from the Late Bronze Age to the Roman Iron Age. Using innovative methods and new techniques, this volume re-examines the results of earlier excavations and places the site in its wider British and European context
Keywords: Sculptor's Cave; Scotland / Antiquities; Antiquities; Scotland